AlSi10MnCuZr alloy for high-performance casting of automobile engine and production process of AlSi10MnCuZr alloy

By adjusting the element content in aluminum alloy and carrying out solid solution treatment and aging treatment, the shortcomings of existing aluminum alloy materials in strength, heat resistance and fatigue resistance are solved, and AlSi10MnCuZr alloy is realized in the casting of high-performance engine parts. Excellent performance.

CN119392048AInactive Publication Date: 2025-02-07WUJIANG XIANDAI ALUMINUM IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411276858.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing aluminum alloy materials are difficult to meet the needs of modern high-performance engines in terms of strength, heat resistance and fatigue resistance.

Method used

AlSi10MnCuZr alloy and its production process are adopted to optimize the structure and performance of the alloy by adjusting the content of elements such as silicon, copper, manganese, and magnesium, combined with solid solution treatment and aging treatment.

Benefits of technology

It improves the hardness, thermal stability and corrosion resistance of the alloy, enhances casting performance and mechanical properties, and is suitable for casting of high-performance automotive engine components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an Al Si 10MnCuZr alloy for high-performance casting of an automobile engine and a production process of the Al Si 10MnCuZr alloy, and relates to the technical field of aluminum alloy materials, and the Al Si 10MnCuZr alloy for high-performance casting of the automobile engine is characterized in that the Al Si 10MnCuZr alloy for high-performance casting of the automobile engine is composed of, by mass, 9.0%-11.0% of silicon (S i), less than or equal to 0.40% of iron (Fe), 0.15%-0.30% of copper (Cu), 0.2%-0.35% of manganese (Mn), and the balance Al and inevitable impurities. The alloy comprises, by weight, 0.28%-0.35% of magnesium (Mg), less than or equal to 0.08% of titanium (Ti), 0.08%-0.12% of zirconium (Zr) and the balance Al and a small amount of impurity elements, the sum of all the components is 100%, the zirconium element is added into the alloy, grains in the alloy can be refined, the strength and toughness of the alloy are improved, meanwhile, casting defects are reduced, the titanium element is further added into the alloy, the tensile strength and hardness of the alloy are improved, and the service life of the alloy is prolonged. Meanwhile, the high-temperature resistance and the fatigue resistance are improved; the production process is simple and efficient, the service safety of the alloy is met, and the application range of the alloy is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloy materials, and more specifically to an AlSi10MnCuZr alloy used for high-performance casting of automobile engines and a production process thereof. Background Art

[0002] Aluminum alloy is the most widely used type of nonferrous metal structural material in industry, and has been widely used in aviation, aerospace, automobile, machinery manufacturing, shipbuilding and chemical industries. The main component of aluminum alloy material is aluminum. Different grades of aluminum alloy mainly have different alloy components and contents, and have different processing properties and performance.

[0003] The engine is the core component of the car, responsible for providing power for the car, and determines the performance and efficiency of the car. At present, the engine materials on the market are mainly cast iron and alloy. Cast iron engine: Cast iron engine is a traditional engine material with high strength and durability, but relatively heavy. Alloy engine: Alloy engine is made of lightweight materials such as aluminum alloy, with advantages such as light weight, high strength and high durability. However, traditional aluminum alloy materials can hardly meet the needs of modern high-performance engines in terms of strength, heat resistance and fatigue resistance.

[0004] Therefore, new solutions need to be proposed to solve this problem. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide an AlSi10MnCuZr alloy for high-performance casting of automobile engines and a production process thereof.

[0006] The above technical purpose of the present invention is achieved through the following technical scheme: an AlSi10MnCuZr alloy for high-performance casting of automobile engines, whose element composition is as follows according to mass percentage: silicon (Si): 9.0%-11.0%, iron (Fe): ≤0.40%, copper (Cu): 0.15%-0.30%, manganese (Mn): 0.2%-0.35%, magnesium (Mg): 0.28%-0.35%, titanium (Ti): ≤0.08%, zirconium (Zr): 0.08%-0.12%, and the remainder is Al and a small amount of impurity elements, and the sum of each component is 100%.

[0007] The present invention is further provided as follows: a production process of AlSi10MnCuZr alloy, for producing the alloy as claimed in claim 1, comprising the following steps:

[0008] S1. Ingredients: Al-Mg-Ti master alloy, Al-Mn master alloy, Al-Cu-Ti master alloy, Al-Fe master alloy, Al-Zr master alloy, pure aluminum and Al-Si alloy are weighed according to the proportion, wherein the number of Al-Zr master alloy is three parts and the number of pure aluminum is ten parts;

[0009] S2. Drying: Dry the alloy material to be smelted to remove surface moisture and impurities;

[0010] S3, coating and drying: applying the coating to the contact surfaces of the graphite clay crucible, the smelting tool and the mold, placing the graphite clay crucible in a smelting furnace to dry, using sandpaper to polish the oxide layer on the surface of the master alloy and pure aluminum, and then placing in a drying oven to dry and preheat;

[0011] S4, smelting: put three parts of Al-Zr master alloy into a graphite clay crucible and preheat them to 450 degrees Celsius, then heat them to 1050 degrees Celsius to melt the Al-Zr master alloy, put in Al-Mn master alloy and Al-Fe master alloy, wait for them to melt and stir them thoroughly, keep them warm and let them stand for 20 minutes, wrap Al-Mg-Ti master alloy, Al-Cu-Ti master alloy and pure aluminum with aluminum foil and put them into a graphite clay crucible, and press them to the bottom of the graphite clay crucible with a slag spoon to reduce oxidation damage, wait for them to melt and stir them thoroughly, keep them warm and let them stand for 20 minutes, and adjust the furnace temperature to 650 degrees Celsius;

[0012] S5, refining: use a slag spoon to skim off the scum on the surface of the alloy solution, add a refining agent, let it stand for 10 to 20 minutes, then skim off the scum on the surface of the alloy solution again, raise the furnace temperature to 700 degrees Celsius, and let it stand for insulation;

[0013] S6, pouring: taking the preheated metal mold out of the constant temperature drying oven, and then pouring the alloy melt obtained in S5 into the mold, and obtaining an alloy ingot after cooling;

[0014] S7, repeated smelting and casting: preparing an Al-Si master alloy, repeating steps S2 to S5 on the alloy ingot 1 and the Al-Si master alloy obtained in S6, drying, smelting, refining and casting the alloy ingot 1 and the Al-Si master alloy to obtain an alloy ingot 2;

[0015] S8. Performing solution treatment and aging treatment on the alloy ingot 2.

[0016] The present invention is further configured as follows: the coating in step S3 is prepared by adding water to zinc oxide and sodium silicate in a ratio of 3:1.

[0017] The present invention is further configured such that the refining agent in step S5 contains C2Cl6 and mixed rare earth elements.

[0018] The present invention is further configured as follows: the solid solution treatment in step S8 adopts bipolar solid solution treatment, the treatment temperature of the first-level solid solution of the bipolar solid solution is 600 degrees Celsius to 650 degrees Celsius, the treatment time of the first-level solid solution is 2 hours to 3 hours, the treatment temperature of the second-level solid solution is 670 degrees Celsius to 700 degrees Celsius, and the treatment time of the second-level solid solution is 3.5 hours to 5 hours.

[0019] The present invention is further configured as follows: the aging treatment in step S8 adopts bipolar aging treatment, the alloy ingot 2 is subjected to solution treatment and then quenching treatment, and then the bipolar aging treatment is performed, the treatment temperature of the primary aging treatment of the bipolar aging treatment is 150 degrees Celsius to 180 degrees Celsius, the treatment time of the primary aging treatment is 6 hours to 8 hours, the treatment temperature of the secondary aging treatment of the bipolar aging treatment is 220 degrees Celsius to 250 degrees Celsius, and the treatment time of the secondary aging treatment is 8 hours to 12 hours.

[0020] In summary, the present invention has the following beneficial effects: the silicon content in the present invention is 9.0%-11.0%, and aluminum is the element with the highest content in the AlSi10MnCuZr alloy, which helps to improve the casting performance and wear resistance of the AlSi10MnCuZr alloy, and improve the hardness and thermal stability of the AlSi10MnCuZr alloy. The iron content in the AlSi10MnCuZr alloy is less than or equal to 0.40%, and the low iron content helps to reduce the impurity phase in the AlSi10MnCuZr alloy, improve the purity and mechanical properties of the alloy, and at the same time, the AlS Microalloying elements such as copper (Cu), manganese (Mn), magnesium (Mg), titanium (Ti) and zirconium (Zr) are added to the AlSi10MnCuZr alloy. These elements play a role in refining grains, improving strength and improving corrosion resistance in the alloy. Titanium and zirconium enhance the comprehensive properties of the alloy by forming stable compounds. The comprehensive properties of the AlSi10MnCuZr alloy are improved by adjusting the content of each element, so that the AlSi10MnCuZr alloy has good casting performance and corrosion resistance while maintaining sufficient strength. DETAILED DESCRIPTION

[0021] The present invention is described in detail below in conjunction with embodiments.

[0022] The invention discloses an AlSi10MnCuZr alloy for high-performance casting of automobile engines and a production process thereof. The AlSi10MnCuZr alloy comprises, by mass percentage, silicon (Si): 9.0%-11.0%, iron (Fe): ≤0.40%, copper (Cu): 0.15%-0.30%, manganese (Mn): 0.2%-0.35%, magnesium (Mg): 0.28%-0.35%, titanium (Ti): ≤0.08%, zirconium (Zr): 0.08%-0.12%, and the remainder is Al and a small amount of impurity elements, and the sum of the components is 100%. The AlSi10MnCuZr alloy improves the casting performance, mechanical strength and heat resistance of the alloy through the synergistic effect of elements such as silicon, copper, manganese and magnesium, and at the same time strictly controls the content of impurity elements such as iron and titanium to ensure the purity and performance stability of the alloy.

[0023] The AlSi10MnCuZr alloy production process is used to produce AlSi10MnCuZr alloy, and includes the following steps:

[0024] S1. Ingredients: Al-Mg-Ti master alloy, Al-Mn master alloy, Al-Cu-Ti master alloy, Al-Fe master alloy, Al-Zr master alloy, pure aluminum and Al-Si alloy are weighed according to the proportion, wherein the number of Al-Zr master alloy is three parts and the number of pure aluminum is ten parts;

[0025] S2. Drying: Dry the alloy material to be smelted to remove surface moisture and impurities;

[0026] S3, coating and drying: applying the coating to the contact surfaces of the graphite clay crucible, the smelting tool and the mold, placing the graphite clay crucible in a smelting furnace to dry, using sandpaper to polish the oxide layer on the surface of the master alloy and pure aluminum, and then placing in a drying oven to dry and preheat;

[0027] S4, smelting: put three parts of Al-Zr master alloy into a graphite clay crucible and preheat them to 450 degrees Celsius, then heat them to 1050 degrees Celsius to melt the Al-Zr master alloy, put in Al-Mn master alloy and Al-Fe master alloy, wait for them to melt and stir them thoroughly, keep them warm and let them stand for 20 minutes, wrap Al-Mg-Ti master alloy, Al-Cu-Ti master alloy and pure aluminum with aluminum foil and put them into a graphite clay crucible, and press them to the bottom of the graphite clay crucible with a slag spoon to reduce oxidation damage, wait for them to melt and stir them thoroughly, keep them warm and let them stand for 20 minutes, and adjust the furnace temperature to 650 degrees Celsius;

[0028] S5, refining: use a slag spoon to skim off the scum on the surface of the alloy solution, add a refining agent, let it stand for 10 to 20 minutes, then skim off the scum on the surface of the alloy solution again, raise the furnace temperature to 700 degrees Celsius, and let it stand for insulation;

[0029] S6, pouring: taking the preheated metal mold out of the constant temperature drying oven, and then pouring the alloy melt obtained in S5 into the mold, and obtaining an alloy ingot after cooling;

[0030] S7, repeated smelting and casting: preparing an Al-Si master alloy, repeating steps S2 to S5 on the alloy ingot 1 and the Al-Si master alloy obtained in S6, drying, smelting, refining and casting the alloy ingot 1 and the Al-Si master alloy to obtain an alloy ingot 2;

[0031] S8. Performing solution treatment and aging treatment on the alloy ingot 2.

[0032] The alloy element content and melting point of each master alloy in step S1 are as follows:

[0033]

[0034]

[0035] The AlSi10MnCuZr alloy is smelted at two sides. In the first smelting, Al-Zr master alloy, Al-Mn master alloy, Al-Cu-Ti master alloy, Al-Fe master alloy, Al-Zr master alloy and pure aluminum are smelted, wherein the number of Al-Zr master alloy is three parts and the number of pure aluminum is ten parts. After smelting, alloy ingot one is obtained, and then alloy ingot one and Al-Si master alloy are smelted to obtain alloy ingot two. The ratio of alloy content ensures that the percentage of each element in the finally obtained AlSi10MnCuZr alloy reaches a predetermined value, thereby ensuring the stability of the AlSi10MnCuZr alloy.

[0036] The raw materials of the coating in step S3 are zinc oxide and sodium silicate, which are mixed in a mass ratio of 3:1. The additive is water, which is used to mix the zinc oxide and sodium silicate into a spreadable coating. The coating is applied to the contact surfaces of the graphite clay crucible, smelting tools and molds to prevent excessive oxidation and contamination during alloy smelting and pouring. By forming a protective layer on the contact surface, the coating helps to reduce the chemical reaction between the alloy melt and the crucible, tools and molds, thereby maintaining the purity and performance of the alloy. After coating, the graphite clay crucible needs to be placed in a smelting furnace for drying to ensure that the coating is firmly attached to the surface, and the oxide layer on the surface of the intermediate alloy and pure aluminum is polished and placed in a drying oven for drying and preheating to further improve the adhesion and protective effect of the coating.

[0037] In step S4, since the melting points of the master alloys are different, when smelting to form an alloy ingot, the high melting point Al-Zr master alloy is added first, the furnace temperature is raised to 1050 degrees Celsius for melting, and then the Al-Mn master alloy and Al-Fe master alloy with similar melting points are added in descending order of melting points. After melting, the master alloy is fully stirred, and the scum on the surface of the alloy solution is skimmed off, and the solution is kept warm and allowed to stand for 20 minutes. Then, the Al-Mg-Ti master alloy, Al-Cu-Ti master alloy and pure aluminum are wrapped with aluminum foil and put into a graphite clay crucible. The slag is pressed to the bottom of the graphite clay crucible with a slag spoon to reduce oxidation damage. After melting, the master alloy is kept warm and allowed to stand for 20 minutes to ensure that the elements have enough time to be evenly distributed in the melt by diffusion and other means, thereby improving the uniformity and organizational properties of the alloy.

[0038] The refining agent used in step S5 contains C2Cl6 and mixed rare earth elements, and the mixed rare earth elements contain Ce, La and Nd. C2Cl6 reacts with aluminum liquid during the aluminum alloy smelting process to generate gas. Hydrogen in the melt enters the bubbles and is compounded into a hydrogen molecule state. At the same time, the bubbles are mixed with the slag and discharged, thereby playing a role in purification and hydrogen removal, and the reaction speed is fast. Rare earth has excellent impurity removal, degassing, strengthening and grain refinement effects. Trace amounts of rare earth can significantly improve the organizational structure of the alloy, thereby improving the strength and processing performance of the alloy.

[0039] In step S7, the steps of S2 to S5 are repeated for the alloy ingot 1 and the Al-Si master alloy obtained by smelting, and the alloy ingot 1 and the Al-Si master alloy are dried, smelted, refined and cast to obtain the alloy ingot 2. Since the melting point of the alloy ingot 1 will decrease after smelting, the graphite clay crucible in step S4 is heated to 700 degrees and then the alloy ingot 1 is added, and it is fully stirred after it is melted. The Al-Si master alloy is wrapped with aluminum foil and put into the graphite clay crucible, and the Al-Si master alloy is pressed to the bottom of the graphite clay crucible with a slag spoon, and it is fully stirred after it is melted. The alloy is kept warm and allowed to stand for 20 minutes. The furnace temperature is adjusted to 650 degrees Celsius, and the alloy melt is subjected to steps S5 and S6 to obtain the alloy ingot 2.

[0040] Step S8 performs solution treatment and aging treatment on the alloy ingot 2 obtained by step S7, the solution treatment adopts bipolar solution treatment, and the aging treatment adopts bipolar aging. The treatment temperature of the first-level solution of bipolar solution is 600 degrees Celsius to 650 degrees Celsius, and the treatment time of the first-level solution is 2 hours to 3 hours. The treatment temperature of the second-level solution is 670 degrees Celsius to 700 degrees Celsius, and the treatment time of the first-level and second-level solution is 3.5 hours to 5 hours. The first-level solution treatment is a low-temperature solution treatment, the purpose of which is to preliminarily dissolve part of the solution elements into the matrix material, while reducing the overburning phenomenon and grain growth that may occur at high temperature. The second-level solution treatment is a high-temperature solution treatment, the purpose of which is to increase the solubility, optimize the material's organizational structure, and prepare for subsequent heat treatment (such as quenching, aging, etc.). The organizational structure and performance of the material can be optimized by bipolar solution treatment. After the alloy ingot 2 is subjected to solution treatment, After quenching, bipolar aging treatment is carried out. The treatment temperature of the first aging treatment of bipolar aging treatment is 150 degrees Celsius to 180 degrees Celsius, and the treatment time of the first aging treatment is 6 hours to 8 hours. At this stage, a high-density GP zone (Guinier-Preston zone) or other fine precipitation phases are mainly formed. These precipitation phases serve as the core of the subsequent aging precipitation phase and help to improve the uniformity of the organization. The treatment temperature of the second aging treatment of bipolar aging treatment is 220 degrees Celsius to 250 degrees Celsius, and the treatment time of the second aging treatment is 8 hours to 12 hours. At this stage, the precipitation phases further grow and transform to form a more stable and evenly distributed precipitation phase structure. These precipitation phases can significantly improve the strength and corrosion resistance of the material. The strength and stress corrosion resistance of the material are improved through bipolar aging treatment, the organization is refined, and the mechanical properties are improved.

[0041] In summary, the AlSi10MnCuZr alloy obtained by the above-mentioned production process and the ratio of each element in the AlSi10MnCuZr alloy has good castability and mechanical properties, especially exhibits good strength, corrosion resistance and wear resistance under high temperature conditions, is suitable for high-performance casting of automobile engine parts, can effectively improve the performance and durability of the engine, can meet the requirements of high-performance automobile engines, and has good practical application value.

[0042] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. An AlSi10MnCuZr alloy for high performance casting of automobile engines, characterized in that: Its elemental composition in terms of mass percentage is: silicon (Si): 9.0% - 11.0%, iron (Fe): ≤0.40%, copper (Cu): 0.15% - 0.30%, manganese (Mn): 0.2% - 0.35%, magnesium (Mg): 0.28% - 0.35%, titanium (Ti): ≤0.08%, zirconium (Zr): 0.08% - 0.12%, the remainder is Al and a small amount of impurity elements, and the sum of all components is 100%.

2. A process for producing an AlSi10MnCuZr alloy, for producing the alloy as claimed in claim 1, characterized in that: The steps include: S1. Ingredients: Al-Mg-Ti master alloy, Al-Mn master alloy, Al-Cu-Ti master alloy, Al-Fe master alloy, Al-Zr master alloy, pure aluminum and Al-Si alloy are weighed according to the proportion, wherein the number of Al-Zr master alloy is three parts and the number of pure aluminum is ten parts; S2. Drying: Dry the alloy material to be smelted to remove surface moisture and impurities; S3, coating and drying: applying the coating to the contact surfaces of the graphite clay crucible, the smelting tool and the mold, placing the graphite clay crucible in a smelting furnace to dry, using sandpaper to polish the oxide layer on the surface of the master alloy and pure aluminum, and then placing in a drying oven to dry and preheat; S4, smelting: put three parts of Al-Zr master alloy into a graphite clay crucible and preheat them to 450 degrees Celsius, then heat them to 1050 degrees Celsius to melt the Al-Zr master alloy, put in Al-Mn master alloy and Al-Fe master alloy, wait for them to melt and stir them thoroughly, keep them warm and let them stand for 20 minutes, wrap Al-Mg-Ti master alloy, Al-Cu-Ti master alloy and pure aluminum with aluminum foil and put them into a graphite clay crucible, and press them to the bottom of the graphite clay crucible with a slag spoon to reduce oxidation damage, wait for them to melt and stir them thoroughly, keep them warm and let them stand for 20 minutes, and adjust the furnace temperature to 650 degrees Celsius; S5, refining: use a slag spoon to skim off the scum on the surface of the alloy solution, add a refining agent, let it stand for 10 to 20 minutes, then skim off the scum on the surface of the alloy solution again, raise the furnace temperature to 700 degrees Celsius, and let it stand for insulation; S6, pouring: taking the preheated metal mold out of the constant temperature drying oven, then pouring the alloy melt obtained in S5 into the mold, and obtaining an alloy ingot after cooling; S7, repeated smelting and casting: preparing an Al-Si master alloy, repeating steps S2 to S5 on the alloy ingot 1 and the Al-Si master alloy obtained in S6, drying, smelting, refining and casting the alloy ingot 1 and the Al-Si master alloy to obtain an alloy ingot 2; S8. Performing solution treatment and aging treatment on the alloy ingot 2.

3. The AlSi10MnCuZr alloy production process according to claim 2, characterized in that: The coating in step S3 is prepared by adding water to zinc oxide and sodium silicate in a ratio of 3:

1.

4. The AlSi10MnCuZr alloy production process according to claim 2, characterized in that: The refining agent in step S5 contains C2Cl6 and mixed rare earth elements.

5. The AlSi10MnCuZr alloy production process according to claim 2, characterized in that: The solution treatment in step S8 adopts bipolar solution treatment, and the treatment temperature of the first-level solution of the bipolar solution is 600 degrees Celsius to 650 degrees Celsius, and the treatment time of the first-level solution is 2 hours to 3 hours. The treatment temperature of the second-level solution is 670 degrees Celsius to 700 degrees Celsius, and the treatment time of the second-level solution is 3.5 hours to 5 hours.

6. The AlSi10MnCuZr alloy production process according to claim 2, characterized in that: The aging treatment in step S8 adopts bipolar aging treatment. The alloy ingot 2 is subjected to solution treatment and quenching treatment, and then the bipolar aging treatment is performed. The treatment temperature of the primary aging treatment of the bipolar aging treatment is 150 degrees Celsius to 180 degrees Celsius, and the treatment time of the primary aging treatment is 6 hours to 8 hours. The treatment temperature of the secondary aging treatment of the bipolar aging treatment is 220 degrees Celsius to 250 degrees Celsius, and the treatment time of the secondary aging treatment is 8 hours to 12 hours.